Peningkatan Keterampilan Menulis Puisi melalui Metode Outdoor Study pada Kelas VIII.A SMP Negeri 4 Tommo Kabupaten Mamuju - Lilisa Karlina; Aco Karumpa; Muhammad Nurahmad (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
This research is classroom action research which aims to improve the poetry writing ability of class VIII.A students through the application of the Outdoor Study method. This research uses a classroom action research design with two cycles. Data was collected through poetry writing tests, observations, and questionnaires. Data analysis was carried out quantitatively and qualitatively. Indicators of research success are an increase in student scores above the KKM (75) and an increase in the quality of written poetry, which includes aspects of diction, sentence structure and depth of meaning. The results of this research provide important implications for the development of learning to write poetry, especially in the context of student-centered and experience-oriented learning. This classroom action research examines the effectiveness of the Outdoor Study method in improving students' poetry writing abilities through two research cycles. The research results showed a significant increase in student involvement and the quality of poetry writing after cycle II. The percentage of students who achieved completeness criteria increased from 43% to 78. Comparison between the two cycles showed significant improvements in various aspects, such as the use of diction, sentence structure, and depth of meaning. The Outdoor Study method has proven to be effective in stimulating creativity and providing meaningful learning experiences for students